Analisis Terhadap Tindak Pidana Terorisme (Studi Perbandingan Jarimah Al-Baghyudalam Perspektif Hukum Islam Dan Hukum Indonesia) - Winda Wulan; Erdianto Effendi; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A criminal act of terrorism is an act committed by an individual or group with the intention of influencing or intimidating another person or group to feel insecure, uncomfortable and end in physical or non-physical destruction. The criminal act of terrorism in Islam is also called Jarimah Al-Baghyu, in the Islamic legal system it has several indicators of similarities and differences with criminal acts of terrorism are regulated in Indonesian positive law, so that the implementation of the law will also create differences. So the purpose of this study is to analyze the criminal act of terrorism in the perspective of Islamic law and Indonesian positive law, as well as the ideal concept of terrorism in the future. The method in this study using research library with normative juridical research approach. Normative legal research is carried out by examining library materials consisting of primary, secondary and tertiary materials. And data collection techniques using literature study and document study. Furthermore, the data analysis uses a comparative analysis method, namely comparing and identifying data obtained from Islamic law and Indonesian law regarding the crime of terrorism. The results of the research show that the regulation of criminal acts of terrorism, seen from its strengths, is binding comprehensively, has a good and systematic structure and there are drawbacks such as the retroactive principle, regarding the provisions of subversive issues, intelligence reports and arrests and the investigation process. And the ideal concept of criminal acts of terrorism in the future takes into account the protection of the community against anti-social acts which harm and endanger it, still by observing the objectives of the crime, namely to reduce crime and control crime, improve the perpetrator, such as rehabilitation, correctionalization and release. As well as regulating and limiting the arbitrariness of the authorities and society in general and protecting the perpetrators for acts outside the lawKeyword: Terrorism, Positive Law, Islamic Law